Associations between subclinical depressive symptoms and reduced brain volume in middle-aged to older adults. (3rd July 2019) - Szymkowicz, Sarah M.; Woods, Adam J.; Dotson, Vonetta M.; Porges, Eric C.; Nissim, Nicole R.; O'Shea, Andrew; Cohen, Ronald A.; Ebner, Natalie C.
ABSTRACT: Objectives: The associations between subclinical depressive symptoms, as well specific symptom subscales, on brain structure in aging are not completely elucidated. This study investigated the extent to which depressive symptoms were related to brain volumes in fronto-limbic structures in a sample of middle-aged to older adults. Method: Eighty participants underwent structural neuroimaging and completed the Beck Depression Inventory, 2nd Edition (BDI-II), which comprises separate affective, cognitive, and somatic subscales. Gray matter volumes were extracted from the caudal and rostral anterior cingulate, posterior cingulate, hippocampus, and amygdala. Hierarchical regression models examined the relationship between brain volumes and (i) total depressive symptoms and (ii) BDI-II subscales were conducted. Results: After adjusting for total intracranial volume, race, and age, higher total depressive symptoms were associated with smaller hippocampal volume ( p = 0.005). For the symptom subscales, after controlling for the abovementioned covariates and the influence of the other symptom subscales, more somatic symptoms were related to smaller posterior cingulate ( p = 0.025) and hippocampal ( p < 0.001) volumes. In contrast, the affective and cognitive subscales were not associated with brain volumes in any regions of interest. Conclusion: Our data showed that greater symptomatology was associated with smaller volume in limbic brain regions. These findings provide evidence for preclinical biological markers of major depression and specifically advance knowledge of the relationship between subclinical depressive symptoms and brain volume. Importantly, we observed variations by specific depressive symptom subscales, suggesting a symptom-differential relationship between subclinical depression and brain volume alterations in middle-aged and older individuals.